2017
DOI: 10.1002/jum.14451
|View full text |Cite
|
Sign up to set email alerts
|

Prospects of Contrast‐Enhanced Ultrasonography for the Diagnosis of Peripheral Arterial Disease: A Meta‐analysis

Abstract: Contrast-enhanced ultrasonography is a valuable tool for the diagnosis of PAD based on its ability to differentiate the time to peak intensity between patients with PAD and healthy individuals, but little data are yet available to assess its diagnostic ability in clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 47 publications
0
11
0
1
Order By: Relevance
“…Some vascular specialists advocate the use of ultrasound contrast agents to improve visualization; however, clinical studies to date are limited. 260 Although multiple studies have shown DUS to be inferior to other imaging techniques, such as DSA, it offers many advantages as a first-line imaging modality, including its noninvasive nature, low cost, no iodinated contrast media, no ionizing radiation, and no fixed installation (mobility). 25,261,262 The main disadvantages of DUS are that it is time-consuming and highly operator dependent, and it does not produce a continuous lesion map.…”
Section: Imaging Of Vascular Anatomymentioning
confidence: 99%
“…Some vascular specialists advocate the use of ultrasound contrast agents to improve visualization; however, clinical studies to date are limited. 260 Although multiple studies have shown DUS to be inferior to other imaging techniques, such as DSA, it offers many advantages as a first-line imaging modality, including its noninvasive nature, low cost, no iodinated contrast media, no ionizing radiation, and no fixed installation (mobility). 25,261,262 The main disadvantages of DUS are that it is time-consuming and highly operator dependent, and it does not produce a continuous lesion map.…”
Section: Imaging Of Vascular Anatomymentioning
confidence: 99%
“…40,41 Ultrasound contrast agents (CEUS) to evaluate PAD was aimed to assess physiopathology and muscular reserve in normal or with clinical suspicion of peripheral arterial insufficiency patients, or to improve diagnostic accuracy of vascular arterial mapping. 42,43 In contrast to extracranial carotid arteries, there is a lack of reference guidelines on how to perform DUS of the lower limb arterial tree in diabetic patients with or without foot lesions. Also, there is no clear idea on what the benefits of using DUS before revascularization would be.…”
Section: Us In the Diagnosis Management And Followup Of Peripheral mentioning
confidence: 99%
“…Ultrasound contrast agents (CEUS) to evaluate PAD was aimed to assess physiopathology and muscular reserve in normal or with clinical suspicion of peripheral arterial insufficiency patients, or to improve diagnostic accuracy of vascular arterial mapping. 42,43…”
Section: Ultrasound In the Ischemic Diabetic Footmentioning
confidence: 99%
“…Неинвазивность, отсутствие нефротоксичности, возможность многократного повторения исследования, меньшая стоимость в сравнении с инвазивными методами диагностики увеличивают ценность этого исследования [10]. Возможно применение ультразвукового сканирования с контрастным усилением, но исследований по оценке эффективности этой методики пока недостаточно [11].…”
Section: особенности диагностики атеросклеротического поражения у пациентов с синдромом диабетической стопыunclassified